SIKAP, NORMA SUBJEKTIF DAN KONTROL KEPRILAKUAN PRAKTIK PEMBIAYAAN NASABAH KOPERASI SYARIAH di KABUPATEN BOGOR (Equilibrium: Jurnal Ekonomi Syariah, 2018)
This study aims to measure the normative attitude and behavior sharia cooperative customers in Bogor District. This type of research is a quantitative research. The data used using primary data through questionnaire. The results of this study indicate that attitudes and norms of belief have a significant or positive influence on customers' intentions to finance the sharia financial services cooperative in Bogor. Other results achieved by sharia cooperatives must improve performance to give more impression of honesty and what is in accordance with religious sharia. Where the advantages of sharia names will be more prominent than the conventional name, it is also to improve trust, evaluation, motivation and behavior of customers in financing the sharia financial services cooperatives. So that the financing intentions in accordance with the sharia can be realized properly.